2021
DOI: 10.1097/hjh.0000000000002963
|View full text |Cite
|
Sign up to set email alerts
|

N-glycosylation of immunoglobulin G predicts incident hypertension

Abstract: Objectives: Glycosylation of immunoglobulin G (IgG) is an important regulator of the immune system and has been implicated in prevalent hypertension.The aim of this study is to investigate whether the IgG glycome begins to change prior to hypertension diagnosis by analysing the IgG glycome composition in a large population-based female cohort with two independent replication samples.Methods: We included 989 unrelated cases with incident hypertension and 1628 controls from the TwinsUK cohort (mean follow-up tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Changes in IgG glycosylation from “young” to “old” glycome associate with many health risks that accompany menopause ( Martinić Kavur et al., 2021 ). In some diseases such as rheumatoid arthritis ( Ercan et al., 2010 ; Gudelj et al., 2018b ) and cardiovascular diseases ( Kifer et al., 2021 ; Menni et al., 2018 ; Wittenbecher et al., 2020 ), this change was shown to occur years before disease onset, suggesting the causal role of IgG glycans in disease development. Proinflammatory IgG glycome and the resulting decrease in the ability of IgG to suppress low-grade chronic inflammation may be an important molecular mechanism that mediates the increased health risk in perimenopause, thus this topic should be studied in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in IgG glycosylation from “young” to “old” glycome associate with many health risks that accompany menopause ( Martinić Kavur et al., 2021 ). In some diseases such as rheumatoid arthritis ( Ercan et al., 2010 ; Gudelj et al., 2018b ) and cardiovascular diseases ( Kifer et al., 2021 ; Menni et al., 2018 ; Wittenbecher et al., 2020 ), this change was shown to occur years before disease onset, suggesting the causal role of IgG glycans in disease development. Proinflammatory IgG glycome and the resulting decrease in the ability of IgG to suppress low-grade chronic inflammation may be an important molecular mechanism that mediates the increased health risk in perimenopause, thus this topic should be studied in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…BP was measured by a trained nurse and performed with the patient in the sitting position for 3 minutes as previously described. 27 The cuff was placed on the subject's arm so that it was approximately 2-3 cm above the elbow joint of the inner arm, with the air tube lying over the brachial artery. The subject's arm was placed on the table or supported with the palm facing upwards, so that the tab of the cuff was placed at the same level of the heart.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiovascular diseases (CVD) are the main cause of mortality, and Kifer et al, recently identified four IgG N-glycan traits that associate with an increased risk of incident hypertension. 295 Three glycan traits, representing simple glycan structures containing a core fucose with only one or no galactose residues attached to the bisecting N-acetylglucosamine, significantly increase in individuals who developed hypertension during follow-up when compared with those defined as controls, whereas only one glycan structure decreases, a more complex digalactosylated structure with two sialic acid residues attached to the galactose molecules and without a bisecting N-acetylglucosamine. These results indicate that the IgG glycoprofile of individuals who would develop incidental hypertension during follow-up manifests a proinflammatory pattern and is associated with obesity years before diagnosis, which indeed supports a role of IgG glycosylation in the incident hypertension.…”
Section: Ht-glycomics In Epidemiological Studiesmentioning
confidence: 99%
“…Interestingly, several IgG glycans strongly correlated with the expected lifespan, suggesting that IgG glycome composition may correlate with all-cause mortality risk. Cardiovascular diseases (CVD) are the main cause of mortality, and Kifer et al, recently identified four IgG N -glycan traits that associate with an increased risk of incident hypertension . Three glycan traits, representing simple glycan structures containing a core fucose with only one or no galactose residues attached to the bisecting N -acetylglucosamine, significantly increase in individuals who developed hypertension during follow-up when compared with those defined as controls, whereas only one glycan structure decreases, a more complex digalactosylated structure with two sialic acid residues attached to the galactose molecules and without a bisecting N -acetylglucosamine.…”
Section: Applicationsmentioning
confidence: 99%